2011
DOI: 10.5565/rev/papers/v97n4.408
|View full text |Cite
|
Sign up to set email alerts
|

El impacto del intercambio de música sobre la compra de discos y la asistencia a conciertos. El caso de España

Abstract: ResumenEn la última década, el intercambio de archivos a través de Internet ha pasado de ser un fenómeno circunscrito a una minoría de la población, a convertirse en un fenómeno de gran impacto a nivel social, mediático, económico y político. El motivo no es otro que la percepción de un elemento de causalidad directa entre el incremento de las descargas y la disminución de las compras de bienes culturales como los discos de música. Es lo que hemos denominado la perspectiva de la sustitución utilitarista. No ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Herrera-Usagre (2012) endeavors to study in an empirical way the connections between downloading and buying, and downloading and attending live performances in people’s conduct through the Survey of Cultural Practices Habits ( Encuesta de hábitos de prácticas culturales ) (SGAE, 2007). It concludes that if individuals exchange more records, they will buy more of them in physical format, and, consequently, they are more willing to attend live performances.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Herrera-Usagre (2012) endeavors to study in an empirical way the connections between downloading and buying, and downloading and attending live performances in people’s conduct through the Survey of Cultural Practices Habits ( Encuesta de hábitos de prácticas culturales ) (SGAE, 2007). It concludes that if individuals exchange more records, they will buy more of them in physical format, and, consequently, they are more willing to attend live performances.…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the other hand, around a 6% more CDs were sold than in 2020 (https://es.statista.com/estadisticas/474727/musica-fisica-espanola-variacion-de-volumen-de-ventas-espana-por-tipo/). Some authors have called this phenomenon as the perspective of utilitarian substitution and have identified that certain factors such as educational level, age, socioprofessional situation of the life cycle associated with fatherhood or motherhood have influenced the music consumption (Herrera-Usagre, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Personal characteristics [16,20,24,25,32] Socioeconomic factors [20,24,25,32,46,[50][51][52] Human and cultural capital [5,[12][13][14][15][16][17]21,22,53,54] External factors [5][6][7][8]19,23] Some of them highlight characteristics such as age, gender, and socioeconomic level. For example, ref.…”
Section: Factors Referencesmentioning
confidence: 99%
“…Concerning human and cultural capital, ref. [54] tried to make an empirical observation of the relationships of download, purchase, and attendance at concerts in the behaviour of individuals using the 2007 Cultural Habits and Practices Survey of the Ministry of Culture, applying a least square linear regression and a logistic regression. He concluded that the more records individuals exchange, the more records they buy in physical format and the higher their likelihood to attend concerts.…”
Section: Factors Referencesmentioning
confidence: 99%